Homotaurine limits the spreading of T cell autoreactivity within the CNS and ameliorates disease in a model of multiple sclerosis - Jide Tian (Scientific Reports, 2021)
Abstract Most multiple sclerosis (MS) patients given currently available disease-modifying drugs (DMDs) experience progressive disability. Accordingly, there is a need for new treatments that can limit the generation of new waves T cell autoreactivity that drive disease progression. Notably, immune cells express GABAA-receptors (GABAA-Rs) whose activation has anti-inflammatory effects such that GABA administration can ameliorate disease in models of type 1 diabetes, rheumatoid arthritis, and COVID-19. Here, we show that oral GABA, which cannot cross the blood–brain barrier (BBB), does not affect the course of murine experimental autoimmune encephalomyelitis (EAE). In contrast, oral administration of the BBB-permeable GABAA-R-specific agonist homotaurine ameliorates monophasic EAE, as well as advanced-stage relapsing–remitting EAE (RR-EAE). Homotaurine treatment beginning after the first peak of paralysis reduced the spreading of Th17 and Th1 responses from the priming immunogen to a new myelin T cell epitope within the CNS. Antigen-presenting cells (APC) isolated from homotaurine-treated mice displayed an attenuated ability to promote autoantigen-specific T cell proliferation. The ability of homotaurine treatment to limit epitope spreading within the CNS, along with its safety record, makes it an excellent candidate to help treat MS and other inflammatory disorders of the CNS.